A NEW SPECIES OF GOBIID FISH MONISHIA BULEJIENSIS (TELEOSTEI; GOBIIDAE) FROM THE KARACHI COAST - Hoda, S M Shamsul (Indian Journal of Fisheries, 2011)
Monishia bulejiensis, a new species of gobiid flsh, is described and figuredfrom the Karachi coast, Pakistan. It is distinguished from other species of thegenus by the possession of an orbital tentacle and by its characteristic generalcolouration.